The Schur–Weyl duality for the unitary group of a II1-factor - Nessonov, N. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
We obtain an analogue of the Schur–Weyl duality for the unitary group of an arbitrary II1-factor.